A review on some of mechanical properties and durability of high- performance self- compacting concretes - Fathollah Sajedi (Iranian Society of Structrual Engineering (ISSE), 2020)
Concrete density is always a problem that occurs during concrete and it affects the strength, durability and apparent qualities of hardened concrete. Vibration is a practical thing that comes with a lot of noise and requires trained workers, and failure to do so will cause many problems. To overcome this problem, the development of self-compacting concrete has begun. This concrete, fills all the dimensions of the mould and is flowing through the use of more fine-grained and plastic shrinkage, without the need for vibration, without any parts being detached. The topics that have been considered for many years in concrete technology have been resilient and durable. For concrete having self-compacting and high resistance and durability, high- performance self-compacting concrete (HPSCC) has been created. The achievement of self-condensation requires the use of a large amount of powdered material, some of which are capable of replacing part of the cement, and replacing them is a step towards sustainable development. Also, using powder materials, the density of concrete aggregates increases and leads to improved strength and durability. The use of large quantities of powdered materials increases the need for mixing water and the likelihood of plastic shrinkage. Therefore, it is necessary to consider all items to enhance concrete performance, so that HPC can be designed and constructed. Therefore, in this research, a review of previous studies on the nature, mechanical properties and durability of highly capable HPSCC’s has been carried out and about 90 high citation articles have been considered, focusing on goals and results. The results of previous studies have shown that using SCC, concrete with similar strength of conventional concrete can be obtained. By reducing the proportion of water to cementicious materials, as well as using pozzolans, not only resistance but also concrete properties are enhanced and HPSCC is obtained.